Functional properties and health benefits of bioactive peptides derived from Spirulina: A review. Issue 1 (2nd January 2018) - Ovando, Claudia Anahite; Carvalho, Julio Cesar de; Vinícius de Melo Pereira, Gilberto; Jacques, Philippe; Soccol, Vanete Thomaz; Soccol, Carlos Ricardo
ABSTRACT: Bioactive peptides represent specific sequences of amino acids that have biological activity with several health effects and potential applications, which can be obtained from diverse protein sources. Spirulina, the cyanobacterium known for its high protein content and therapeutic properties, has been investigated as a potential source of bioactive peptides. Some bioactive peptides derived from Spirulina are under study for their ability to offer specific health benefits, such as antimicrobial, antiallergic, antihypertensive, antitumor, and immunomodulatory properties. Bioactive peptide fractions from Spirulina biomass can be obtained through a series of operations, including cell lysis and protein extraction, enzymatic hydrolysis, potential bioactivity screening, fractionation, and purification. Potentially, Spirulina -derived peptide fractions can be applied as nutraceutical ingredients in foods and pharmaceuticals. This article reviews the functional properties and health benefits of bioactive peptides from Spirulina, and presents potential mechanisms by which bioactive components can be exploited in the development of novel foods with special health claims. In addition, this article describes recent developments in proteomics, bioactivity screening methods, and opportunities for designing future peptide-based foods.